2019
DOI: 10.1016/j.jad.2019.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Identifying depression in the National Health and Nutrition Examination Survey data using a deep learning algorithm

Abstract: Nutrition Examination Survey (NHANES) datasets using deep learning and machine learning algorithms.  Deep-learning achieved a high performance for identifying depression on the NHANES datasets of both the United States and South Korea.  Trained deep-learning and machine learning algorithms are useful for estimating the prevalence of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 34 publications
2
33
1
Order By: Relevance
“…Previous studies have effectively predicted psychiatric diseases such as depression using large scale data. Similar to our study, one research team has predicted patients of depression in the general population with an AUC of 0.89 using a deep learning technique based on K-NHANES (16). In addition, another group has predicted the response of patients with major depressive disorder to selective serotonin reuptake inhibitors with an AUC of 0.82 by deep learning (40).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Previous studies have effectively predicted psychiatric diseases such as depression using large scale data. Similar to our study, one research team has predicted patients of depression in the general population with an AUC of 0.89 using a deep learning technique based on K-NHANES (16). In addition, another group has predicted the response of patients with major depressive disorder to selective serotonin reuptake inhibitors with an AUC of 0.82 by deep learning (40).…”
Section: Discussionsupporting
confidence: 61%
“…Recently, deep learning has been actively used to screen and predict psychiatric diseases based on these predictors (15). A recent study has effectively identified patients with depression based on data of a large-scale survey from the United States, the National Health and Nutrition Examination Survey (16). Another study has also identified anxious and depressive participants using socio-demographic, occupational, and healthrelated information (17).…”
Section: Introductionmentioning
confidence: 99%
“…The NHANES and K-NHANES are nationwide surveys that assess the health and nutritional status of the general population in each country. We recently analyzed the NHANES and K-NHANES datasets and classified depression (20). This two-year cross-sectional survey addresses complex, multistage, stratified sampling of the entire population.…”
Section: Datasets and Covariatesmentioning
confidence: 99%
“…Because the device is always connected to the network, data points cannot be lost and the generated data can be automatically saved and configured for later analysis. Future machine learning-based analysis will allow us to predict cholesterol levels and calculate a patient's risk of metabolic disease [16,17].…”
Section: Resultsmentioning
confidence: 99%